Redescriptions of Hypogastruridae and Onychiuridae (Collembola) described by David L. Wray - Bernard, Ernest C. (Zootaxa, 2015)
Species of Hypogastruridae and Onychiuridae described by D. L. Wray were reexamined and redescribed where necessary from type material and other specimens. Mitchellania hermosa is redescribed and transferred to Ceratophysella. Hypogastrura ireneae is redescribed and H. gravesi is validated with additional material. Hypogastrura gami is synonymized with H. humi and H. utahensis is synonymized with H. promatro. A lectotype is designated for Schoettella (Knowltonella) idahoensis. Achorutes magnoliana is confirmed as a synonym of Schoettella glasgowi. Xenylla carolinensis is synonymized with Xenyllodes armatus Axelson (Odontellidae). Onychiurus mai is transferred to the genus Leeonychiurus and becomes L. mai, and O. magninus is transferred to Heteraphorura and becomes H. magnina. Additional details are given for Onychiurus wilchi.